Adaptation of the Cognitive and Affective Mindfulness Scale (CAMS-R) to Indonesian Version and Its Validation: Muslim Mothers-Data Driven - Sutarto Sutarto; Idi Warsah; Khusnul Khotimah; Endang Prastuti; Ruly Morganna (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
CAMS-R is a measurement instrument designed for normal adult participants. There have been a few studies conducting lingua-cultural adaptation of CAMS-R in the Indonesian context, but such studies have not touched on the discourse of Muslim mothers. Accordingly, this study aimed to conduct linguistic adaptation of CAMS-R by translating it into Bahasa Indonesia. Also, it aimed to examine the measurement model to find whether the structure of CAMS-R was confirmed relevant to empirical data or not. At the stage of forward translation, this study involved 5 participants, namely two translators and three psychologists with doctoral academic qualifications. The stage of back translation engaged 3 participants, namely a bachelor in English and two linguistics experts. The pilot study incorporated 10 readers, and the try-out involved 103 Muslim mothers between the ages of 20-40 years old. Data analysis used confirmatory factor analysis (CFA). Results demonstrated that the measurement of mindfulness construct had high goodness of fit. The results of model fit evaluation indicated chi square of 8.742 (p=.557), GFI of .976, AGFI of .932, CFI of 1.000, TLI of 1.014, and RMSEA of .000. The foregoing depicted a good fit of goodness. CAMS-R contained 12 items and left 7 items with loading factors above 0.5. (.585 – .887). Composite reliability (CR) sub-scale resulted in the scores of .713 – .785, and its overall CR scale was .936 and AVE of .736 – .739. The foregoing data indicated good convergent and discriminant validity. This study emphasized that CAMS-R could ideally be used to measure mindfulness for the Indonesian population of Muslim mothers between the ages of 20-40 years.